2005
DOI: 10.1016/j.vetmic.2005.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Cellular composition and interferon-γ expression of the local inflammatory response in feline infectious peritonitis (FIP)

Abstract: Feline infectious peritonitis (FIP) is one of the most important viral diseases of cats. International studies estimate that approximately 80% of all purebred cats are infected with the causative agent, feline coronavirus (FCoV). Out of these, 5-12% develop clinical symptoms of FIP. The pathogenesis of the disease is complex with many unresolved issues relating to the role of the immune system. The aim of the present study was to determine the proportions of various inflammatory cell types in FIP lesions by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 21 publications
4
45
1
Order By: Relevance
“…Although the reason(s) for the predominance of FIP-associated renal lesions is unclear, several factors can be considered as contributory towards the development of these alterations. The kidney is the organ that is more frequently affected in FIP (BERG et al, 2005;ADDIE et al, 2009;PEDERSEN, 2009;MELI, 2014), and retrospective studies have shown that a large percentage of cats have FIP-associated renal disease (OLIVEIRA et al, 2003;NORRIS et al, 2005); these findings are in accordance with the results of our investigation. The kidney has a single circulatory system, receives 20% of the cardiac output, is composed of two distinct capillary beds (glomerular and peritubular capillary network), with a complex array of afferent arterioles, resulting in a blood flow that is approximately 40 times more elevated than the other organs (BLANTZ; GABBAI, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Although the reason(s) for the predominance of FIP-associated renal lesions is unclear, several factors can be considered as contributory towards the development of these alterations. The kidney is the organ that is more frequently affected in FIP (BERG et al, 2005;ADDIE et al, 2009;PEDERSEN, 2009;MELI, 2014), and retrospective studies have shown that a large percentage of cats have FIP-associated renal disease (OLIVEIRA et al, 2003;NORRIS et al, 2005); these findings are in accordance with the results of our investigation. The kidney has a single circulatory system, receives 20% of the cardiac output, is composed of two distinct capillary beds (glomerular and peritubular capillary network), with a complex array of afferent arterioles, resulting in a blood flow that is approximately 40 times more elevated than the other organs (BLANTZ; GABBAI, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Feline monocytes have been previously shown consitutively to express cytokines (Kipar et al 2005), including IFNγ ( Van de Velde et al 2013). Obesity increases both IL-6 and IFNγ transcription in feline adipose tissue (Van de Velde et al 2013) and IFNγ might be a signal of macrophage activation in cats (Berg et al 2005). The macrophage synthesis of NO has also been shown in cats (Ponti et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, although biased by the low number of observations and by the high individual variability, these results suggest that some sequences of FCoV protein N from ''avirulent'' or ''mixed'' strains can stimulate cell-mediated immunity, especially in cats in which cell-mediated immunity is primed by chronic diseases. Future larger studies are required to confirm the possible role of FCoV itself in stimulating the production of IFN-g, the key cytokine of cell-mediated immunity involved in the response against FCoVs and consequently responsible of viral persistence (Gunn-Moore et al, 1998;Dean et al, 2003;Foley et al, 2003;Kiss et al, 2004;Berg et al, 2005;Gelain et al, 2006;Giordano and Paltrinieri, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the development of FIP depends on the balance between humoral and cellular immune response (Pedersen, 2009). The cytokine interferon-g (IFN-g) is one of the main modulators of cell mediated immunity (Berg et al, 2005). IFN-g shifts the immune response from T-helper 2 to T-helper 1 with a consequent enhancement of immune cytotoxic activity due to the activation of macrophages and CD8+ T cells.…”
Section: Introductionmentioning
confidence: 99%